Health evaluation of employees occupationally exposed to methylene chloride: metabolism data and oxygen half-saturation pressures - Ott, M. Gerald; Skory, Lyman K.; Holder, B. B.; Bronson, Julie M.; Williams, Paul R. (Scandinavian Journal of Work, Environment & Health, 1983)
The in vivo metabolism of methylene chloride to form carboxyhemoglobin has been demonstrated in a number of experimental studies. The present investigation was undertaken to quantitate the relationships between methylene chloride exposure, the percentage of carboxyhernoglobin saturation, the alveolar carbon monoxide level, and the oxygen halfsaturation pressure in an occupational setting. As expected, methylene chloride exposure produced dose-related increases in the level of carboxyhernoglobin and alveolar carbon monoxide and a corresponding decrease in the oxygen half-saturation pressure. The calculated decrease in oxygen half-saturation pressure was between 2 and 4 mm Hg (266.6 & 533.3 Pa, respectively) among persons exposed to ≥300 ppm of methylene chloride for an 8-h workday. Additional analyses indicated that this shift in the oxy`hemoglobin dissociation curve could be explained on the basis of the known carbon monoxide interactions with hemoglobin.
Keywords: carboxyhemoglobin; employee; health evaluation; hemoglobin oxygen affinity; metabolism; metabolism data; methylene chloride; occupational exposure; oxygen half-saturation pressure; oxygen pressure; oxygen transport